Community Size as a Factor in Health Partnerships in Community Parks and Recreation, 2007 - Laura L. Payne, PhD; Jo An M. Zimmermann, PhD; Andrew J. Mowen, PhD; Elizabeth Orsega-Smith, PhD; Geoffrey C. Godbey, PhD (Centers for Disease Control and Prevention, 2013)
Introduction Although partnerships between park and recreation agencies and health agencies are prevalent, little research has examined partnership characteristics and effectiveness among communities of different sizes. The objective of this study was to determine whether park and recreation leaders' perceptions of partnership characteristics, effectiveness, and outcomes vary by community size. Methods A web-based survey was completed in 2007 by 1,217 National Recreation and Park Association members. Community size was divided into 4 categories: very small, small, medium, and large. Questions measured agencies' recognition of the need for partnerships, their level of experience, and the effectiveness and outcomes of partnerships. Results Larger communities were significantly more likely to recognize the need for and have more experience with partnerships than smaller communities. Very small and large communities partnered significantly more often with senior services, nonprofit health promotion agencies, and public health agencies than did small and medium ones. Large and small communities were significantly more likely than very small and medium communities to agree that their decision making in partnerships is inclusive and that they have clearly defined goals and objectives. Large communities were significantly more likely than very small communities to report that their partnership helped leverage resources, make policy changes, meet their mission statement, and link to funding opportunities. Conclusion Community size shapes partnership practices, effectiveness, and outcomes. Very small communities are disadvantaged in developing and managing health partnerships. Increasing education, training, and funding opportunities for small and rural park and recreation agencies may enable them to more effectively partner with organizations to address community health concerns.